Diseño de una planta para generación de energía eléctrica a partir de energía mareomotriz en la zona de bajo baudó (2023)
In this project, a financial feasibility study will be carried out for a conceptual design of a tidal energy micropower plant in Bajo Baudó, Choco, Colombia. It will start with the approach to the problem from different perspectives and the research will be limited to the solution to a social problem from an engineering perspective. In addition, terms and basic concepts for its development. It should be noted that, in the development of the project, a conceptual and basic design is established, which allows you to select the micro-central equipment from the search for concepts, the analysis of the problem based on the different scenarios and finally, propose one of the possible solutions to the problem. This development will be worked from the macro to the micro, starting from the definition of the potential of use of the municipality and more specifically the selected point. From this, carries out the conceptual design, focusing on the main equipment needed to implement a system such as the hydraulic turbine and electric generator, also a definition of the reservoir to present a basic system and, finally, the study of the main equipment, the turbine, in order to select the best option for it. The project will follow the procedure of the flow chart prepared which can be seen in Figure 1.